EFFECT OF ACUPUNCTURE ON THE FUNCTION OF THE VISUAL SYSTEM IN PATIENTS OF GLAUCOMA - I. V. Valueva (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
At present, significant advances have been made in the surgical and conservative treatment of glaucoma. However, in patients with a prolonged course of the disease, even against the background of normalized intraocular pressure, progressive deterioration of visual functions occurs with the transition of the disease to a more severe stage. Effects directed solely at lowering the intraocular pressure are not able to fully ensure the preservation of visual functions, so its normalization cannot ensure the stabilization of the glaucoma process. Dysfunction of the nervous system and vascular disorders play a significant role in the pathogenesis of glaucoma. In this regard, the treatment of this disease should be comprehensive and include neuroprotective therapy aimed at correction of metabolic disorders that occur in glaucoma in the optic nerve head, improvement of local microcirculation and trophism of tissues, normalization the rheological properties of the blood. Conventional conservative therapy does not provide adequate blood supply to the optic nerve and prevent the deterioration of visual functions in more than half of patients. The purpose of this study was to study the effectiveness of reflexotherapy in patients with glaucoma after surgery and normalization of intraocular pressure. In the study, 18 patients with a diagnosis of primary open-angle glaucoma were treated. It has been established that reflexotherapy improves significantly the functions of the visual system and the general condition, normalizes arterial pressure and psycho-emotional state of patients.